Modelling avian influenza in bird-human systems : this thesis is presented in the partial fulfillment of the requirement for the degree of Masters of Information Science in Mathematics at Massey University, Albany, New Zealand - Zhao, Yue (Massey University, 2009)
In 1997, the first human case of avian influenza infection was reported in Hong Kong. Since then, avian influenza has become more and more hazardous for both animal and human health. Scientists believed that it would not take long until the virus mutates to become contagious from human to human. In this thesis, we construct avian influenza with possible mutation situations in bird-human systems. Also, possible control measures for humans are introduced in the systems. We compare the analytical and numerical results and try to find the most efficient control measures to prevent the disease.
Keywords: Bird flu; Mathematical modelling; Zoonoses; Disease control; Fields of Research::280000 Information, Computing and Communication Sciences::280400 Computation Theory and Mathematics::280404 Numerical analysis